Chronic cutaneous varicella zoster virus infection complicating dermatomyositis. Issue 4 (31st January 2014) - Hoesly, Fridolin J.; Sluzevich, Jason C.
Abstract Chronic cutaneous varicella zoster virus (VZV) infection has not been previously reported or characterized as a complication of dermatomyositis. Two patients with non‐malignancy‐associated dermatomyositis, treated with long‐term prednisone and methotrexate, developed persistent, painless ulcers ultimately established to be secondary to chronic VZV. The absence of pain or a history suggestive of acute VZV, and the lack of characteristic histopathology, resulted in a lengthy delay in diagnosis. Polymerase chain reaction and tissue immunohistochemistry were positive for VZV, and treatment with valacyclovir resulted in complete clearance. Diagnostic testing for VZV should thus be considered in the evaluation of ulcerative lesions in patients with dermatomyositis. The increased incidence of acute VZV in combination with the nature and duration of immunosuppressive treatment in this patient population may be contributory.